2022
DOI: 10.1111/ejn.15882
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychological distress associates with alterations in resting‐state low‐frequency fluctuations and distal functional connectivity of the neonate medial prefrontal cortex

Abstract: Prenatal stress exposure (PSE) has been observed to exert a programming effect on the developing infant brain, possibly with long-lasting consequences on temperament, cognitive functions and the risk for developing psychiatric disorders. Several prior studies have revealed that PSE associates with alterations in neonate functional connectivity in the prefrontal regions and amygdala. In this study, we explored whether maternal psychological symptoms measured during the 24th gestational week had associations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 101 publications
1
3
0
Order By: Relevance
“…Our finding of lower functional connectivity of the MPFC and left PFC with other brain regions is in line with earlier findings of prenatal distress follow-up studies using brain imaging techniques. Firstly, our results are in line with a very recent study from the FinnBrain Birth Cohort study: Rajasilta et al ( 2023 ) also reported altered MPFC functional connectivity in neonates prenatally exposed to maternal stress. Secondly, our results are in line with the finding that offspring of women (highly) psychologically distressed during pregnancy, show altered structural or functional connectivity of the prefrontal cortex with other brain areas (Hay et al, 2020 ; Humphreys et al, 2020 ; Qiu et al, 2015 ; Soe et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of lower functional connectivity of the MPFC and left PFC with other brain regions is in line with earlier findings of prenatal distress follow-up studies using brain imaging techniques. Firstly, our results are in line with a very recent study from the FinnBrain Birth Cohort study: Rajasilta et al ( 2023 ) also reported altered MPFC functional connectivity in neonates prenatally exposed to maternal stress. Secondly, our results are in line with the finding that offspring of women (highly) psychologically distressed during pregnancy, show altered structural or functional connectivity of the prefrontal cortex with other brain areas (Hay et al, 2020 ; Humphreys et al, 2020 ; Qiu et al, 2015 ; Soe et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…More than a decade of brain imaging research has shown that maternal psychological distress during pregnancy, including depression and anxiety, affects the developing fetal brain, with later life consequences for offspring’s cognition and mental health (for a review, see Adamson et al, 2018 ; Dufford et al, 2021 ; Pulli et al, 2019 ; Van den Bergh et al, 2018 ). Recent studies found evidence for changes in offspring’s structural grey matter (e.g., Acosta et al, 2019 , 2020 ; Donnici et al, 2021 ; Moog et al, 2021 ) and white matter (e.g., Demers et al, 2021 ; Manning et al, 2022 ; Rifkin-Graboi et al, 2015 ) as well as functional brain changes, including resting-state functional connectivity (rsFC) using fMRI (e.g., Humphreys et al, 2020 ; Manning et al, 2022 ; Rajasilta et al, 2023 ; Scheinost et al, 2020 ) and task-based fMRI studies (e.g., Mennes et al, 2020 ; van der Knaap et al, 2018 ). Several pioneering studies have even started to show that the timing of these brain alterations is prenatally, by studying the offspring in utero with fetal resting-state fMRI (De Asis-Cruz et al, 2020 ; Thomason et al, 2021 ; van den Heuvel et al, 2021 ; Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rajasilta et al demonstrated that in infants approximately one moth of age maternal prenatal psychological distress was positively linked to rs-fMRI-derived fractional amplitude of low-frequency fluctuations (fALFF) in the neonate mPFC which indicates that prenatal stress may affect functional features of the maturing brain during gestation (Rajasilta et al, 2023). Children of mothers who experienced psychological distress during late pregnancy had increased amygdala functional connectivity with the ventromedial prefrontal cortex (vmPFC) and anterior insula (Marr et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this approach has been utilized to investigate the neural mechanisms underlying the efforts undertaken to achieve long-term goals among people experiencing chronic stress in various professional fields [26,27]. Furthermore, several previous studies evaluated the neurobiological bases of stress-induced clinical conditions, including depression and anxiety, using the fALFF approach [28][29][30]. Therefore, fALFF approach is a promising approach to investigate the neural substrates of SOC in medical professionals.…”
Section: Introductionmentioning
confidence: 99%